MUḤAMMAD NAṢR AL-DÎN AL-ALBÂNÎ AND HIS METHOD OF CORRECTING AND WEAKENING THE HADITH: A CRITICAL READING - Farida, Umma (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
This article aims to describe Muḥammad Naṣr al-Dîn al-Albânî as one of the contemporary scholars who have devoted his efforts in the field of Hadith Science. He believes that the ability to determine the truth or falsity of a hadith not only limited to being done by the earlier clerics, even present scholars may also pass judgment on the validity or weakness of a hadith which is not rated yet by the earlier scholars because according to him, the assessment of hadith is ijtihad which is not stopped until now. By researching some of the work of al-Albânî in the field of hadith, the study is expected to contribute ideas related to al-Albânî method in judgment on the validity or weakness of hadith, and to analyze the consistency of application of his method in the validation of hadith and weaken it. This research shows that al-Albânî followed his discretionary approach, so it is not surprising that many people criticize, given his frequent retreat from his corrections and weaknesses, and the proof of the contradictory provisions of one hadith in different places, and his disorder in documenting narrators.